The Meaning of Religion in Drug Rehabilitation Patients - Saeful Fikri; Mohammad Eisa Ruhullah (Tashwirul Afkar, 2022)
There is a religious problem in today's modern life, such as a shift in religious values, which is indicated by the high rate of drug use among youths. In reality, these teens' primary motivation for doing drugs is to fulfill their curiosity about the drugs because adolescence is a psychologically curious enough stage of life. As a result, several measures try to reduce drug usage, one of which is to conduct rehabilitation based on religion, as was done at Inabah XX. This article will define religiosity in terms of belief, rituals, intellectual, experience, and consequence dimensions for drug rehabilitation patients. This study uses a qualitative methodology to gather data through observation, documentation, and interviewing procedures. Based on the collected data, the researchers discovered that drug rehabilitation patients fully believe in Islamic religious doctrines, including the presence of God, angels, prophets, sacred books, heaven, and hell. The Inabah program demonstrates a rise in diversity in religious practices, including fasting, prayer, and Qur’anic recitation. The inner serenity that rehabilitation patients experience is influenced by how obediently they perform dhikr and prayers. However, this ran contrary to how strictly they fast. Most of them are pretty ignorant regarding religion, but others are well-informed since they have studied religion since they were young. In terms of practice, the majority of them have managed to avoid drinking and thieving. Nevertheless, a few people still find it impossible to stop doing these forbidden acts.